1994
DOI: 10.1080/02783199409553564
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical and verbal reasoning as predictors of science achievement

Abstract: Analyses of the relative contribution of age, gender, verbal reasoning ability, and mathematical reasoning ability as predictors of success in fast-paced science courses are reported in this study. SAT-V and SAT-M were used as indicators of verbal and mathematical reasoning ability respectively and success was indicated by a standardized posttest score. Verbal reasoning ability was found to be a stronger predictor than any of the other individual variables. The amount of required reading varies for biology, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
(2 reference statements)
3
12
0
1
Order By: Relevance
“…The results from our study suggest reinterpretation of the relationship of science to reading and mathematics, respectively, since reading achievement did have a larger effect on science achievement than mathematics achievement. This was consistent with Gustin and Corazza's (1994) finding that verbal ability contributed more to overall science achievement than mathematics ability. To respond correctly on a science test, students must be able to comprehend what is being asked, and therefore reading ability is as important as and possibly even more important than mathematics ability.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results from our study suggest reinterpretation of the relationship of science to reading and mathematics, respectively, since reading achievement did have a larger effect on science achievement than mathematics achievement. This was consistent with Gustin and Corazza's (1994) finding that verbal ability contributed more to overall science achievement than mathematics ability. To respond correctly on a science test, students must be able to comprehend what is being asked, and therefore reading ability is as important as and possibly even more important than mathematics ability.…”
Section: Discussionsupporting
confidence: 90%
“…Data from the TIMSS showed a moderate correlation between mathematics and science achievement scores of eighth graders (Wang, 2005). As described above, Gustin and Corazza (1994) showed that mathematics was a significant predictor of science test scores with high achieving junior high and high school students, although verbal ability and gender contributed more to the model. Importance of Reading and Mathematics Achievement.…”
Section: Relationship Of Reading and Mathematics Achievement To Scienmentioning
confidence: 73%
See 3 more Smart Citations